Pelatihan Desain Grafis Kreatif untuk Ibu-ibu PKK: Meningkatkan Keterampilan dan Produktivitas di Desa Gebanganom Wetan - Muhammad Syifa’ Nuqoba; Ansol Boy; Ainur Rofiq; Ahmad Dani Hilmi; Andika Khuser; Dian Novita Sari; Isroiyah Isroiyah; Isna' Zulvia Khairani; Sulistio Sulistio (Lembaga Pengembangan Kinerja Dosen, 2024)
Creative graphic design training for PKK mothers in Gebanganom Waton Village aims to improve the skills and productivity of PKK members through the use of modern design technology. This article evaluates the training conducted, which covered the basics of graphic design, the use of design software, and practical applications in daily activities. The training was designed to empower PKK mothers in creating promotional materials, community documents, and attractive visual designs. The results of the training showed significant improvements in the design skills of participants, as well as improvements in the efficiency and quality of their work output. This article also discusses the challenges faced during the training and provides recommendations for the implementation of similar training programs in the future, to further support the development of local communities through digital skills